Anatomical-Foliar Diversity of Agave salmiana subsp. salmiana (Asparagaceae) in Three Populations of the Teotihuacán Region (Mexico) - Estela Sandoval-Zapotitla; Lorena E. Chávez-Güitrón; Florencia del C. Salinas-Pérez; Ulises Rosas; Alejandro Vallejo-Zamora (Plants)
Agave salmiana Otto ex Salm-Dyck is an endemic Mexican plant distributed from 1230 to 2460 m above sea level, native to the arid zones of central and southern Mexico. It is a traditionally used species, with morphotypes ranging from wild to cultivated, with an ample cultural and management history. The species is important because it generates employment, and its products are used for self-consumption and are marketed as raw materials; however, little is known about its leaf anatomical description or studies that report the variation in its characters in terms of its level of management and its altitudinal gradient. To address this, we collected leaf samples from three localities of the Teotihuacan region in the State of Mexico (Mexico) and obtained anatomical leaf sections; with these, we also obtained thirty-eight parameters to quantitatively describe leaf anatomy. Thus, in this study, the general anatomical description of the leaf of Agave salmiana subsp. salmiana is presented. Unique leaf characters and others shared with the species of the genus were identified for the leaf of A. salmiana subsp. salmiana. In addition, significant variation was observed when comparing the three sampled localities (78.95%). From the analysis of anatomical characters, abaxial outer periclinal wall length, length of adaxial palisade parenchyma cells, fiber length, surface area of abaxial epidermal cells, width of abaxial palisade parenchyma cells, and total length of parenchyma in adaxial palisade were found to distinguish individuals from the three localities analyzed and the differences are related to management and altitude gradients.